2015
DOI: 10.1371/journal.pone.0120371
|View full text |Cite
|
Sign up to set email alerts
|

Nontypeable Haemophilus influenzae Induces Sustained Lung Oxidative Stress and Protease Expression

Abstract: Nontypeable Haemophilus influenzae (NTHi) is a prevalent bacterium found in a variety of chronic respiratory diseases. The role of this bacterium in the pathogenesis of lung inflammation is not well defined. In this study we examined the effect of NTHi on two important lung inflammatory processes 1), oxidative stress and 2), protease expression. Bronchoalveolar macrophages were obtained from 121 human subjects, blood neutrophils from 15 subjects, and human-lung fibroblast and epithelial cell lines from 16 subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 35 publications
2
53
1
Order By: Relevance
“…Moreover, bacterial colonisation of the respiratory tract in COPD patients is believed to be dynamic, as the bacterial flora frequently changes in terms of both strains and species, although the above‐mentioned bacteria remain prominent 129 . These bacterial pathogens undoubtedly worsen a patient's health over a long period of time and may be a major driver of airway luminal inflammation and oxidative stress, 128 , 130 , 131 , 132 , 133 as well as increased daily symptoms in COPD patients 134 . Indeed, COPD patients chronically colonised with H. influenzae during stable phase showed increased airway inflammation and reduced lung volumes when compared with non‐chronically colonised patients 135 …”
Section: The Role Of the Microbiome In Copdmentioning
confidence: 99%
“…Moreover, bacterial colonisation of the respiratory tract in COPD patients is believed to be dynamic, as the bacterial flora frequently changes in terms of both strains and species, although the above‐mentioned bacteria remain prominent 129 . These bacterial pathogens undoubtedly worsen a patient's health over a long period of time and may be a major driver of airway luminal inflammation and oxidative stress, 128 , 130 , 131 , 132 , 133 as well as increased daily symptoms in COPD patients 134 . Indeed, COPD patients chronically colonised with H. influenzae during stable phase showed increased airway inflammation and reduced lung volumes when compared with non‐chronically colonised patients 135 …”
Section: The Role Of the Microbiome In Copdmentioning
confidence: 99%
“…Reports have demonstrated that inhibitors of the NADPH-oxidase system including diphenylene iodonium reduce MET formation, although this has not been consistent across all studies [23,25,28,29,40]. King et al [47] used a fluorescent readout of ROS production (dihydrorhodamine 123) to indicate that human alveolar macrophages producing METs had a 2-fold increase in ROS fluorescence compared to cells not forming METs. Treating alveolar macrophages with the ROS inhibitor apocinin inhibited MET release.…”
Section: Cellular Pathways Implicated In Met Releasementioning
confidence: 99%
“…In combination with parallel ex vivo human sample and primary cell culture analysis, they provide powerful tools for exploring these associations and are valuable for testing new drugs. [7][8][9]53,57,170 Translatability into humans can be addressed by applying treatments specifically to those patients with alterations in drug targets. Through similar analysis of comparable tissues from mice and humans, using similar techniques such as the interrogation of precision-cut lung slices, important therapeutic questions can be examined in future COPD studies.…”
Section: Utility Of Mouse Models and New Translational Techniquesmentioning
confidence: 99%